PENGARUH RASIO KEUANGAN TERHADAP KONDISI FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2009-2012 - Jevi Wulan Yuliana, 10.05.52.0062; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2014)
The purpose of this study was to determine the variables that can explain the prediction of financial distress at the manufacturing company. This research was conducted to test the hypothesis (hypotheses testing) the proposed research, where variables current ratio, cash ratio, quick ratio, ROA, ROE, GPM, NPM, ToTA, ToTE, LdTE, SG, TATo, WCTo, dan iNTo to explain the financial distress condition on manufacturing companies. There are from 116 listed manufacturing firms in Indonesia Stock Exchange (IDX). Period of analysis is 2009-2012. The sample consists of 116 manufacturing firms were split into two 63the condition of financial distress for companies that are experiencing financial distress and 53 financial distress condition for companies that are experiencing non distress. The statistical methods used to test the hypothesis is logistic regression analysis and methods of sampling used is purposive sampling. Result financial ratios a significance affect on financial distress, such ratio is ROA. ThenÂ current ratio, cash ratio, quick ratio, ROA, ROE, GPM, NPM, ToTA, ToTE, LdTE, SG, TATo, WCTo, dan iNTo not significance on financial distress. Keywords: financial distress, financial ratio, and logistic regression